Senior High School Students References in Choosing Orthodontic Treatment Provider: A Study in Marelan Subdistrict 2018 - Feni Firdanigrum; Kintoko Rochadi; Ameta Primasari (Britain International of Humanities and Social Sciences (BIoHS) Journal, 2020)
Initially the use of orthodontic appliance (braces) was intended to tidy up the teeth that had an irregular shape. The phenomenon of braces is increasingly prevalent among teenagers because in addition to health reasons then developed into a reason to support the appearance and eventually become a self-identity for adolescents. Finally, there are more victims of dental artisans who report disruption of oral health due to the installation of braces on dental artisans. Because the installation is not in accordance with the medical standard. The purpose of this study was to determine how senior high school student choose orthodontic treatment provider. To achieve these objectives, research was conducted using independent variables, namely knowledge, cost, distance, family support. The subjects of this study were 105 senior high school students. The subjects were taken using non-probability sampling and purposive sampling techniques. The data analysis method used is multiple linear regression test by taking into account the simultaneous test, classic assumption and partial test, correlation test determinant. The results of this study indicate that the variable cost (p=0, 0001), distance (p=0,014) and consumer knowledge (p=0,014) significantly influence the dependent variable (consumer decision) while the family support variable (p = 1,000) has no effect. Different from family (p = 1,000 > 0.05) support that has no relationship with consumer decision-making to choose orthodontic treatment provider, service costs (p = 0, 0001 < 0, 05), the distance traveled by respondents (p = 0.014 <0.05) and knowledge of respondents (p = 0.014 <0.05) have relationship with consumer decision making to choose orthodontic treatment provider both in Public and Private High Schools, and Public and Private Vocational Schools in Marelan Subdistrict, respectively.